2021
DOI: 10.3390/ijerph18168459
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Workplace Violence Prevention in Emergency Departments: A Systematic Review

Abstract: Emergency departments (EDs) are high-risk settings for workplace violence, but interventions to prevent violent incidents and to prepare staff are not yet consistently implemented, and their effectiveness is often unclear. This study aims to summarise evidence on workplace violence prevention interventions that were implemented in EDs to reduce violent incidents caused by patients/relatives or to increase the knowledge, skills or feelings of safety of ED staff. A systematic review was conducted. The databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 35 publications
0
33
0
3
Order By: Relevance
“…Furthermore, Chinese ED nurses still fail to take actions to protect themselves even after WPV, and the most important one is to submit a violence report. According to previous studies, submitting violence reports is of great importance in improving organizational management and obtaining psychological support, which will benefit all staff in the emergency departments [ 19 , 46 ]. In addition, the top three reasons for WPV were unmet patients’ need, long waiting times, and alcohol/drug abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Chinese ED nurses still fail to take actions to protect themselves even after WPV, and the most important one is to submit a violence report. According to previous studies, submitting violence reports is of great importance in improving organizational management and obtaining psychological support, which will benefit all staff in the emergency departments [ 19 , 46 ]. In addition, the top three reasons for WPV were unmet patients’ need, long waiting times, and alcohol/drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale studies about HCWs have already been established [ 13 , 14 ], and prospective studies [ 15 , 16 ] and longitudinal studies [ 17 , 18 ] as well. However, only small-scale cross-sectional studies, sample size was less than 500, about ED nurses were done in China and abroad [ 5 , 19 ]. Therefore, a large-scale and thorough research on WPV and its predictors among Chinese ED nurses is a necessity.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review without meta-analysis carried out with 15 studies revealed that most of them exerted a positive effect on preparing the team to deal with violent situations or on reducing the number of violent incidents, although the evidence is still scarce (59) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of multiple approaches such as education and support services seemed to be effective, as a mixed approach showed significant effects [43]. Thus, interventions using mixed approaches may be more effective, especially if combined with the use of technology (e.g., wearables, monitoring systems) that could track episodes of violence while maintaining the privacy of patients and HCWs [44]. Globally, individuals are increasingly vulnerable and at risk of violence [29], with significant economic and social consequences.…”
Section: Discussionmentioning
confidence: 99%